STRATEGI PENGEMBANGAN PADI LOKAL SPESIFIK LOKASI DI KABUPATEN KAPUAS PROVINSI KALIMANTAN TENGAH - Erlina, Yuni; Elbaar, Evi Feronika; Wardie, Jhon (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
Rice cultivation on sub-optimal land, in fact, the output is still very diverse, this requires special attention and treatment for farmers and researchers. In Kapuas district, planting local rice is one part of local wisdom that must be maintained. This study aims to examine local rice development strategies for specific locations on tidal peatlands. Data analysis using SWOT and QSPM analysis. SWOT results support an aggressive strategy for local rice / rice development in Kapuas District. The results of the QSPM analysis showed that the program priority of the Total Attractiveness Score (TAS) strategy was 6.371, with strategic policies through market development, optimal business management, expansion of rice processing businesses with organized activities, keeping maintenance sustainability of rice cultivation sawah pasang surut, giat farmer group institutionalization, increasing cooperation with the government, as well as improving the quality of human resources for young farmers.